2018
DOI: 10.37358/rc.18.10.6618
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal Colonization and Pneumococcal Disease in Children with Influenza Clinical, laboratory and epidemiological features

Abstract: We retrospectively studied clinical features of the 2015-2016 paediatric influenza season and the rate of pneumococcal colonization/disease in a reference Romanian infectious diseases institute. Peak influenza activity occurred between weeks 5-10/2016; A viruses initially predominated, switching to B viruses after week 12/2016. Patients� median age was 4.4 years. Patients with influenza A were significantly younger compared with influenza B (p[0.001), and required longer hospitalization (p[0.001). S. pneumonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…Clinical characteristics of influenza did not differ significantly between elderly patients with influenza A and B in our study. This is in line with previous research from our institute in children 14 and from France in all age groups, showing that clinical characteristics are mostly indistinguishable between viral types and subtypes 15 . Among the SARI criteria, fever and odynophagia associated higher odds of testing positive for influenza in our study; this is consistent with the data reported by Falsey et al, which showed that the combination of fever with cough or odynophagia exhibited the best balance of sensitivity and specificity for diagnosing influenza 16 .…”
Section: Discussionsupporting
confidence: 93%
“…Clinical characteristics of influenza did not differ significantly between elderly patients with influenza A and B in our study. This is in line with previous research from our institute in children 14 and from France in all age groups, showing that clinical characteristics are mostly indistinguishable between viral types and subtypes 15 . Among the SARI criteria, fever and odynophagia associated higher odds of testing positive for influenza in our study; this is consistent with the data reported by Falsey et al, which showed that the combination of fever with cough or odynophagia exhibited the best balance of sensitivity and specificity for diagnosing influenza 16 .…”
Section: Discussionsupporting
confidence: 93%
“…A similar biphasic predominance was observed during the previous 2016–2017 season among hospitalized patients from the same region, although by contrast, only B/Victoria-lineage and A/H3 viruses were identified [7]. Also, unlike previous seasons at our hospital [7, 14], influenza A viruses were detected in ILI admissions throughout the 2017–2018 season and, unusually, all four subtyped viruses (A/H1, A/H3, and both B lineage viruses) were identified in meaningful numbers.…”
Section: Discussionsupporting
confidence: 64%
“…Influenza hospitalizations of young, otherwise healthy children have been frequently reported in previous seasons at the same hospital [7] and at other public healthcare facilities in Romania [5]. Young children have a higher risk of developing severe influenza illness as well as other complications (e.g., bacterial superinfections [14]), which emphasizes the importance of vaccination for this age group [1]. Individuals with chronic illnesses also account for a large proportion of influenza hospitalizations in Romania.…”
Section: Discussionmentioning
confidence: 99%
“…In our population, we have seen a predominance of pediatric patients among cases of LCI. While this may reflect to a certain extent a real increased circulation of influenza viruses among young children, who are known to be a risk group for influenza, this may also be driven at least in part by an increased addressability of pediatric patients with ILI to tertiary care rather than primary care services in our country, as previously discussed [19,20]. Furthermore, a potential propensity towards managing fever and administering antiviral treatment in children in the hospital rather than as outpatients cannot be ruled out, and this is probably reflected in the rather short 5 days median length of hospitalization in infants and toddlers.…”
Section: Plos Onementioning
confidence: 87%